On Testing of Hypotheses for Many Independent Objects - Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2021)
The problem of many hypotheses testing for a model consisting of three independent objects is considered. It is supposed that M probability distributions are known and each object independently of others follows to one of them. The matrix of asymptotic interdependencies (reliabilityreliability functions) of all possible pairs of the error probability exponents (reliabilities) in optimal testing of this model is studied. This problem was introduced (and solved for the case with two given probability distributions) by Ahlswede and Haroutunian. The model with two independent objects with M hypotheses was examined by Haroutunian and Hakobyan.